Calculation and Test of Root Bending Stress Under Load-history Including Friction - Zhou Changjiang; Xie Yaning; Huang Cao; Qian Xuanlü (Jixie chuandong)
The effect of tooth surface friction from mesh- in to mesh- out on bending strength is researched,including the normal and friction force of the driving gear. Based on the variation of tooth surface friction,the engaging region is divided into the upper and lower regions bounded by pitch circle,and then the calculation equations of root stress in different meshing regions are derived. The case shows that the root bending stress with friction is 3% bigger than the one without friction in the upper region,but that the stress with friction is 4% smaller than the one without friction in the lower region. The mutation of the root bending stress is in line with the direction reverse of friction force at pitch point. The experimental and calculating results show that the curves of root bending stress are basically consistent and that the deviation is within 10% when the dynamic load factor is considered in the calculation equations. The calculation model preliminarily is verified by the experimental results,and the calculation equation of tooth root bending stress including friction is more reliable.